Epigenetically-driven anatomical diversity of synovial fibroblasts guides joint-specific fibroblast functions - Frank-Bertoncelj, M; Trenkmann, M; Klein, K; Karouzakis, E; Rehrauer, H; Bratus, A; Kolling, C; Armaka, M; Filer, A; Michel, BA; Gay, RE; Buckley, CD; et al. (Nature Publishing Group, 2017)
A number of human diseases, such as arthritis and atherosclerosis, include characteristic pathology in specific anatomical locations. Here we show transcriptomic differences in synovial fibroblasts from different joint locations and that HOX gene signatures reflect the joint-specific origins of mouse and human synovial fibroblasts and synovial tissues. Alongside DNA methylation and histone modifications, bromodomain and extra-terminal reader proteins regulate joint-specific HOX gene expression. Anatomical transcriptional diversity translates into joint-specific synovial fibroblast phenotypes with distinct adhesive, proliferative, chemotactic and matrix-degrading characteristics and differential responsiveness to TNF, creating a unique microenvironment in each joint. These findings indicate that local stroma might control positional disease patterns not only in arthritis but in any disease with a prominent stromal component.